2008
DOI: 10.1021/ef800343j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Air-Staging on Anthracite Combustion and NOx Formation

Abstract: Experiments were carried out in a multipath air inlet one-dimensional furnace to assess NO x emission characteristics of the staged combustion of anthracite coal. These experiments allowed us to study the impact of pulverized coal fineness and burnout air position on emission under both deep and shallow air-staged combustion conditions. We also studied the impact of char-nitrogen release on both the burning-out process of the pulverized coal and the corresponding carbon content in fly ash. We found that air-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 24 publications
3
73
1
Order By: Relevance
“…Fan et al (2008;2010) investigated the effect of air staging on the NOx emission of anthracite and lignite at 1300 °C in a multi-path air inlet one-dimensional furnace. It was observed that the air-staging ratio had a great effect on NOx formation, and NOx emission decreased with the decrease in stoichiometric ratio of 1.5 to 1.0.…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al (2008;2010) investigated the effect of air staging on the NOx emission of anthracite and lignite at 1300 °C in a multi-path air inlet one-dimensional furnace. It was observed that the air-staging ratio had a great effect on NOx formation, and NOx emission decreased with the decrease in stoichiometric ratio of 1.5 to 1.0.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Therefore, NO in the DFC was mainly transformed by the fuel-N and NH 3 . Figure 11 shows the profiles of NO concentration along the axis of the DFC under different conditions of the secondary air nozzles.…”
Section: Resultsmentioning
confidence: 99%
“…Nasserzadeh et al indicated that the modification of the secondary air orifice can help reduce emissions and optimize the overall plant performance of the incinerator [4,5]. The reduction of NOx emissions has also been achieved on the basis of the air staging conditions in the wall-fired boiler [6][7][8]. Some researchers described the importance of the secondary air jet configuration on the flow path and temperature distributions through CFD analyses [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%